Molecular Breeding of Forage and Turf : The Proceedings of the 8th International Symposium on the Molecular Breeding of Forage and Turf - Budak, Hikmet; Spangenberg, German (Springer International Publishing : Imprint: Springer, 2015)
This proceeding covers all of the collected research data and presentations from the 8th International Symposium on the Molecular Breeding of Forage and Turf. This book explores themes in molecular breeding of forage and turf, including abiotic and biotic stresses, bioenergy and biorenewables, comparative genomics, emerging tools for forage and turf research, and functional genetics and genomics. This work also analyzes genetic mapping of germplasm, diversity and its impact on breeding, herbage quality, plant-microbe interactions, and risk assessment of transgenic plants. Written by renowned researchers in plant genomics, Molecular Breeding of Forage and Turf: The Proceedings of the 8th International Symposium on the Molecular Breeding of Forage and Turf is a valuable resource for researchers and students in the field of plant genomics.